Accuracy of cotinine serum test to detect the smoking habit and its association with periodontal disease in a multicenter study (2017)
The validity of the surveys on self-reported smoking status is often questioned because smokers underestimate cigarette use and deny the habit. It has been suggested that self-report should be accompanied by cotinine test. This report evaluates the usefulness of serum cotinine test to assess the association between smoking and periodontal status in a study with a large sample population to be used in studies with other serum markers in epidemiologic and periodontal medicine researches. 578 patients who were part of a multicenter study on blood biomarkers were evaluated about smoking and its relation to periodontal disease. Severity of periodontal disease was determinate using clinical attachment loss (CAL). Smoking was assessed by a questionnaire and a blood sample drawn for serum cotinine determination. The optimal cut-off point for serum cotinine was 10 ng/ml. Serum cotinine showed greater association with severity of CAL than self-report for mild-moderate CAL [OR 2.03 (CI95% 1.16-3.53) vs. OR 1.08 (CI95% 0.62-1.87) ] advanced periodontitis [OR 2.36 (CI95% 1.30- 4.31) vs. OR 2.06 (CI95% 0.97-4.38) ] and extension of CAL > 3 mm [ OR 1.78 (CI95% 1.16-1.71) vs. 1.37 (CI95% 0.89-2.11)]. When the two tests were evaluated together were not shown to be better than serum cotinine test. Self-reported smoking and serum cotinine test ≥ 10ng/ml are accurate, complementary and more reliable methods to assess the patient's smoking status and could be used in studies evaluating serum samples in large population and multicenter studies. The serum cotinine level is more reliable to make associations with the patient's periodontal status than self-report questionnaire and could be used in multicenter and periodontal medicine studies.